An Integrated Human-Centered Framework as a Pedagogical Approach in Design Education (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study examined how an integrated human-centered pedagogical framework shapes students’ learning experiences in design education, with particular attention paid to the interaction between affective engagement, reflective interpretation, and meaning-making. This research responds to the growing need for design education approaches that move beyond a primary focus on technical skills toward more holistic and interpretive learning processes. Method: A qualitative approach was employed, involving 60 students enrolled in the Commercial and Service Design course within the Visual Communication Design program at Universitas Ciputra. Learning activities were implemented through project-based tasks grounded in human-centered design principles. Data were collected from students’ reflective writing and documentation of their design processes throughout the course. Interpretive thematic analysis was conducted to identify patterns related to affective engagement, reflective interpretation, and meaning-making within students’ learning experiences. Results: The findings indicated that students experienced the learning process as an integrated interaction between emotional engagement, reflection, and contextual interpretation. Emotional responses, such as curiosity, uncertainty, and empathy, encouraged deeper involvement in the design process and stimulated reflective thinking. Through reflection, students articulated the reasoning behind their design decisions and connected contextual understanding with visual problem-solving. Students also demonstrated a shift in perspective, increasingly recognizing visual communication as a contextual and meaning-oriented practice rather than as a purely aesthetic activity. Novelty: Although this study does not propose a new pedagogical model, it provides empirical evidence explaining how affective engagement, reflection, and meaning-making interact within human-centered design learning environments to support experiential and interpretive learning in design education.